Utilization of Gliricidia Sepium Leaf Meal as Protein Source in Diets of Mozambique Tilapia, Oreochromis Mossambicus (Piscs: Cichlidae) - Temesgen, Gebeyehu Gebre-Michael (2004)
A series of experiments were conducted to evaluate the use of tropical fodder legume, Gliricidia sepium leaf as a potential source of protein in the diet of Mozambique tilapia, Oreochromis mossambicus. The effect of leaf age (plant leaf harvesting time) on crude protein (CP) and crude fiber (CF) contents of Gliricidia sepium were determined. G. sepium trees were pruned and leaf samples were taken monthly for five months. Results from chemical analyses of leaves revealed that in terms of its crude protein content, G. iv sepium leaves need to be harvested within 1-3 months after cutting. Leaves harvested from older trees tend to contain less protein. The chemical composition and apparent protein digestibility (APD) of Gliricidia sepium leaves by tilapia, O. mossambicus, were also investigated. G. sepium leaf meal was found to contain high (26.0%) crude protein but low in essential amino acids such as histidine, isoleucine, leucine, phenylalanine, valine and methionine. The apparent protein digestibility was found to be about 56%. In addition, G. sepium has the high crude fiber content. The optimum inclusion level of G. sepium leaf meal in tilapia (O. mossambicus) diet was also determined. Six diets containing 0%, 10%, 25%, 40%, 50% and 88% G. sepium leaf meal were prepared and fed at 4% per body weight per day for 27 g tilapia for 70 days. Growth performances data obtained revealed that the optimum inclusion level of G. sepium leaf meal is 40% of the total diet. Inclusion of G. sepium leaf meal above this level resulted in lower growth of O. mossambicus. The effect of different feeding rate on the performance of G. sepium leaf meal as O. mossambicus diet was also evaluated. Fish were fed diet containing 40% G. sepium leaf meal at 2%, 3%, 4% and 5% per fresh body weight per day. Data on growth and feed utilization performances showed v that O. mossambicus can be fed diet containing 40% G. sepium leaf meal at two percent of wet body weight per day. This feeding rate resulted in statistically comparative growth and feed utilization performance by the tilapia with 3%, 4% and 5% feeding rates. In addition to these, two processing methods of G. sepium leaf meal were compared. Three diets were prepared: 1) a control diet (using fishmeal as sole protein source), 2) oven-dried and 3) presoaked and dried G. sepium leaf meal. The diets were fed to O. mossambicus fingerlings for 70 days. Growth and feed utilization performances of O. mossambicus showed that the three diets resulted in similar performances. It was therefore concluded that G. sepium leaf meal can be used as oven-dried (unsoaked) meal. This might be due to the fact that the major anti-nutritional factors found in this legume are so low in the leaf part of the plant.